Synthetic Biology Brings New Opportunity for Antibiotics Discovery (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are facing a complicated public health issue in the form of global drug shortages, including antibiotics. Synthetic biology empowers the next generation of antibiotics development, bringing us into a new era.